Pronounced effect of hapten binding on thermal stability of an anti-(4-hydroxy-3-nitrophenyl)acetyl antibody possessing a glycine residue at position 95 of the heavy chain. (May 2017) - Sato, Yusui; Inaba, Satomi; Fukada, Harumi; Azuma, Takachika; Oda, Masayuki
Highlights: We analyzed effects of somatic mutation on antigen binding and stability using scFvs. Thermal stability of Tyr95-type is higher than that of Gly95-type. Gly95-type greatly gains thermal stability upon hapten binding. BCR stability would correlate with B-cell population. Abstract: Immune response to T-cell-dependent antigens is highly dynamic; several B-cell clones responsible for antibody production appear alternately during immunization. It was previously shown that at least two-types of antibodies are secreted after immunization with (4-hydroxy-3-nitrophenyl)acetyl (NP); one has Tyr and another has Gly at position 95 of the heavy chain (referred to as Tyr95- and Gly95-type). The former appeared at an early stage, while the latter appeared at a late stage, i.e., after secondary immunization, although Fv domains of these antibodies were encoded by same genes of variable heavy and light chains. We examined whether any biophysical properties of antigen-combing sites relate to this shift in B-cell clones by preparing single-chain Fv (scFv). Thermodynamic and kinetic parameters of the interaction of scFv with various haptens are in accordance with those of intact antibodies, indicating that scFvs are appropriate models for the study on structure and function of antibodies. Next, we measured thermal stability of scFvs using differential scanning calorimetry and found that the apparent melting temperature of free Tyr95-type was 64–66 °C, while that of Gly95-type was 47–48 °C, indicating that the latter was highly unstable. However, Gly95-type greatly gained thermal stability because of hapten binding. We discussed the relationship between thermal stability resulted by hapten binding and dynamism of antibody response during immunization.